Masyarakat Muslim Kamboja Pasca Rezim Khmer Merah: Penindasan, Perlawanan, dan Kebangkitan - Pipi Emi Julianti; Yana Safitri; Reka Seprina (Prabayaksa: Journal of History Education, 2025)
The Muslim community in Cambodia, primarily composed of Cham and Malay ethnic groups, faced severe persecution under the Khmer Rouge regime (1975–1979). The regime’s repressive policies included the suppression of religious freedom, destruction of places of worship, and executions of Muslim leaders and figures. This oppression led to resistance, although the Muslim uprising in Cambodia was quickly suppressed. After the fall of the Khmer Rouge in 1979, the Cambodian Muslim community began rebuilding their lives. This revitalization process included restoring international networks, economic recovery, rebuilding religious and educational infrastructure, and fighting for civil rights. This study employs a historical approach using heuristic methods, source criticism, interpretation, and historiography. The findings indicate that following the fall of the Khmer Rouge, the Cambodian Muslim community gradually regained their rights and started contributing to Cambodia’s social, economic, and political landscape.